2015
DOI: 10.1074/jbc.m115.642645
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the First Cathelicidin from Sea Snakes with Potent Antimicrobial and Anti-inflammatory Activity and Special Mechanism

Abstract: Background: Cathelicidins are a family of vertebrate antimicrobial peptides that play pivotal roles in host immune defense against microbial invasions. Results: A novel cathelicidin (Hc-CATH) with potent antimicrobial and anti-inflammatory activity and a special mechanism was identified from the sea snake Hydrophis cyanocinctus. Conclusion: Hc-CATH is a potent candidate for the development of peptide antibiotics. Significance: Hc-CATH is the first cathelicidin identified from sea snakes and possesses a special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
180
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(187 citation statements)
references
References 45 publications
7
180
0
Order By: Relevance
“…Similar to the extensive research on antimicrobial activity, LPS neutralization has been shown in multiple studies for at least 13 different cathelicidins from 9 different species18434557585960616263646566. Therefore, it is thought to be one of the main cathelicidin functions.…”
Section: Discussionmentioning
confidence: 84%
“…Similar to the extensive research on antimicrobial activity, LPS neutralization has been shown in multiple studies for at least 13 different cathelicidins from 9 different species18434557585960616263646566. Therefore, it is thought to be one of the main cathelicidin functions.…”
Section: Discussionmentioning
confidence: 84%
“…LLKKK18 induces rapid resolution of the inflammatory stage through early M2 macrophage recruitment and stimulates angiogenesis. Yet another HDP that exhibits potent anti-inflammatory activity by inhibiting LPSinduced NO and pro-inflammatory cytokine including TNF-α, IL-6, and IL-1β production is a cathelicidin from the sea snake Hydrophis cyanocinctus [74]. The mode of action is reported to be competitive binding to the Toll-TLR4/MD2 complex, preventing LPS attachment and subsequent activation of LPS-induced inflammatory response pathways.…”
Section: Pro-and Anti-inflammatory Activitiesmentioning
confidence: 99%
“…In addition, venom has been shown to have pro- and anti-inflammatory properties and has been shown to regulate the expression of inflammatory mediators such as IL-1β, IL-6, IL-10, IL-22, TNF-α, PGD2, PGE2, and TXA2 [18,19,21,41,42,43,44]. In this study, we constructed and screened an H. cyanocinctus venom gland T7 phage display library and discovered H-TL1, a natural peptide with antagonizing effects against TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Venom from sea snakes is more streamlined and stable than that from land snakes [20], and Hydrophis cyanocinctus , a primary sea snake species in China, has been used to treat rheumatism for centuries. Wei et al reported a novel cathelicidin (Hc-CATH) from the H. cyanocinctus sea snake that exhibits potent anti-inflammatory activity by inhibiting pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 [21]. Furthermore, hydrostatin-SN1, which was identified by screening a H. cyanocinctus venom gland T7 phage display library, exhibited significant anti-inflammatory activity in a DSS-induced acute colitis mouse model [22].…”
Section: Introductionmentioning
confidence: 99%